Mejoramiento en la eficiencia del proceso de secado convencional y homogenización en el color de la Albura y el Duramen en madera de Teca (Tectona grandis L.) (Documento I) - Berrocal-J., Alexander; Moya-Roque, Roger; Rodríguez-S., María; Muñoz-A., Freddy (Instituto Tecnológico de Costa Rica. Vicerrectoría de Investigación y Extensión (VIE). Escuela de Ingeniería Forestal. Centro de Investigación en Innovación Forestal (CIF), 2016)
Different drying schedules were investigated to decrease drying time of Tectona grandis L. wood from juvenile plantations, using the drying rate (DR) to reduce time. The DR value was 20% per day during the first stages and by the time the wood reached 30% of moisture content (MC), the DR remained in 8% per day until the end of drying. The initial moisture content (MCi) ranged between 92 and 115%, MCi was affected by grain pattern and heartwood percentage. The final moisture content (MCf) differed in 2.0% in relation to the MC targeted for this study. Drying time can be reduced from 140 hours to 105 hours, maintaining DR conditions and saving 33% of energy consumption. DR is affected by moisture content and drying time and this behavior can be modeled mathematically by the equation Y = a*t + b. In these relations, the factors with greatest influence were dry-bulb temperature and wet-bulb depression. Both relations show an inflexion point in the relation DR-MC, 80% in fast drying schedule and 40% in slow drying schedule. This MC indicates the point where the DR must be changed.
Informe final de Proyecto de Investigación. Código: 5401-1401-1030
Keywords: Mejoramiento; Eficiencia; Secado; Color; Madera; Improvement; Efficiency; Wood; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area technology::Forest engineering